THE PREVALENCE OF MALOCCLUSION AND ORTHODONTIC TREATMENT NEED IN A SAMPLE OF SYRIAN CHILDREN - Alatrach, Ayhab B.; Saleh, Fayez K.; Osman, Esam (European Scientific Journal, ESJ, 2014)
Knowledge of a population’s epidemiological situation is vital in planning and provision of dental health services. The present study was undertaken to determine the prevalence of malocclusion and orthodontic treatment need in Syrian children. A randomly selected sample of 200 Syrian children aged between 8 and 13 years was collected from three different public schools in Damascus. For each participant, the records were a pair of dental study casts and a frontal intra-oral photograph. Firstly, Angle’s classification was used to classify malocclusion and the treatment need was assessed utilizing the Aesthetic Component (AC) and the Dental Health Component (DHC) of the Index of Orthodontic Treatment Need (IOTN). The treatment demand was also evaluated in association with gender and the connection between the two components of IOTN was statistically ascertained. The results of the study showed that more than one third of the subjects in the sample were in moderate to great need for orthodontic treatment. No significant difference in treatment need was found between genders and a statistically significant association was expressed between the two components of IOTN.